Bruxism repercussions in muscular activation: Ultrasound differences in abdominal wall between women with and without bruxism. A cross-sectional study. - Paula Yela-Lorenzo; Paola Montes-Arenas; Vanesa Abuín-Porras; Ángel González-de-la-Flor; Laura González-Fernández; Jorge Hugo Villafañe; Isabel Mínguez-Esteban (PLoS ONE)
Introduction Bruxism, often triggered by stress, induces temporomandibular alterations, increasing muscle activity and affecting dental occlusion. Prevalence of musculoskeletal conditions related to stress is higher in women, with craneo-cervical affectation being frequently reported. Moreover, some authors explore the relationship between temporomandibular disorders and postural alteration, affecting the trunk complex. This study aims to evaluate differences in abdominal muscle morphology between women with and without bruxism in Spain, and, secondarily, the effects of voluntary teeth grinding in abdominal muscle activation. Methodology An observational analytical cross-sectional study was conducted with 44 Spanish women (diagnosed with bruxism = 22, non-bruxism = 22). To ensure and corroborate the absence of bruxism from the control group, the Clinical Based Assesment questionnaire was used. Ultrasound measures of Transverse Abdominal, External Oblique and Internal oblique were recorded during rest and voluntary grinding. Results Grinding was associated with changes in abdominal muscle thickness in both groups, with statistically significant higher thickness values for all studied muscles. Moreover, the Bruxism group showed statistically significant higher values for all muscles in grinding conditions compared to the Non-Bruxism group. Significant differences in left transverse abdominal thickness were found between groups in resting condition. Further analysis using linear regression indicated that both Bruxism (t = -2.03, p = 0.049) and BMI (t = 3.13, p = 0.003) were significantly associated with muscle thickness, with BMI acting as a confounding factor. Age was not a significant predictor (p = 0.506), suggesting its limited role in this context. Conclusion The results of this study support the existence of an association between bruxism and the abdominal wall muscles structure and activation. This emphasizes the importance of considering bruxism in the evaluation of abdominal muscle function.